Perilaku Keuangan Generasi Milenial: Memahami Pola Pengambilan Keputusan Keuangan pada Generasi Digital - Enny Istanti; Andrianto Andrianto; RM Bramastyo KN (AKUNTANSI 45, 2025)
The millennial generation, born between 1980 and 2000, is currently the focus of attention in various aspects of life, including in terms of financial behavior. This study aims to analyze the financial behavior of the millennial generation and identify factors that affect the financial behavior of the millennial generation, such as financial literacy, lifestyle, technology and social media, and the social environment. This study uses a qualitative approach with a survey method. Data was obtained through interviews with millennial generation respondents. The millennial generation tends to be more comfortable using digital platforms to manage their finances, including mobile banking and investment applications. The millennial generation has a tendency to prioritize experiences and lifestyles over the accumulation of traditional assets. Those who have higher education and stable jobs tend to exhibit more planned and long-term oriented financial behavior. One of the main findings is the significant influence of digital technology on the financial behavior of the millennial generation. Financial influencers on social media have a significant influence on the investment decisions of the millennial generation. This can explain some patterns of financial behavior that seem irrational from a traditional economic perspective.